Effect of Fertigation on Banana Biometric Characteristics and Fertilizer Use Efficiency - Kumar, Ashok; Kumar, Arvind; Singh, H K; Kumari, N; Kumar, Pramod (Journal of Agricultural Engineering, 2009)
Study was conducted at the Horticultural Experimental Farm, Birauli, Rajendra Agricultural University, Pusa during 1998-1999 to find out effect of the different doses of fertilizer under fertigation on phenological characteristics such as plant height, plant girth, root development; on fruiting time and bunch charactenstics as well as saving in fertilizer. The obtained results revealed that, treatment T1 with 100% of recommended dose of fertilizer (RDF), NPK under drip fertigation gave highest values of plant height, plant girth and average number of leaves followed by treatment T2 with 80 % of RDF. Also, this treatment caused earlier bunch shooting. bunch harvesting as well as fruiting time. The highest bunch weight. number of hands/bunch and number of fingers/bunch with best finger quality (weight, length and diameter) were recorded In T1. Lower values were obtained in treatment with T3 with 60% RDF in drip irrigated treamnent and T4 with 100% of RDF under traditional method of fertilizer application. Maximum yield of banana was obtained in treatment T1 (95.2 t.ha?¹) followed by T2 (87.6 t.ha?¹), T4 (76.4 t.ha?¹) and T3 (73.1 t.ha?¹). The treatment T1 and T2 gave 24.5% and 14.6% more yield. respectively in comparison to control treatment. The result indicated that application of only 65% of RDF can give the yield at par with conventional cultivation. The water and fertilizer use efficiency was about 25% higher for drip fertigated plot in comparison to check basin method of irrigation and fertilizer application through soil manipulation method.